2016
DOI: 10.1002/2015wr017876
|View full text |Cite
|
Sign up to set email alerts
|

Identifying long‐term empirical relationships between storm characteristics and episodic groundwater recharge

Abstract: Shallow aquifers are an important source of water resources and provide base flow to streams; yet actual rates of groundwater recharge are difficult to estimate. While climate change is predicted to increase the frequency and magnitude of extreme precipitation events, the resulting impact on groundwater recharge remains poorly understood. We quantify empirical relations between precipitation characteristics and episodic groundwater recharge for a wide variety of geographic and land use types across North Carol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 54 publications
3
30
0
Order By: Relevance
“…Many of the same factors driving RPR in North Carolina (Tashie et al, ) were found to be important here. Tashie et al () also found a negative correlation between RPR and precipitation magnitude and rate and a positive correlation between RPR and duration, an effect that was more pronounced in developed versus undeveloped areas. The decrease in RPR with larger magnitude events (Figure a) was expected due to greater dominance of overland flow in large magnitude storms (Tashie et al, ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Many of the same factors driving RPR in North Carolina (Tashie et al, ) were found to be important here. Tashie et al () also found a negative correlation between RPR and precipitation magnitude and rate and a positive correlation between RPR and duration, an effect that was more pronounced in developed versus undeveloped areas. The decrease in RPR with larger magnitude events (Figure a) was expected due to greater dominance of overland flow in large magnitude storms (Tashie et al, ).…”
Section: Discussionsupporting
confidence: 61%
“…Tashie et al () also found a negative correlation between RPR and precipitation magnitude and rate and a positive correlation between RPR and duration, an effect that was more pronounced in developed versus undeveloped areas. The decrease in RPR with larger magnitude events (Figure a) was expected due to greater dominance of overland flow in large magnitude storms (Tashie et al, ). We would expect that in an urban area with infiltration of stormwater, there would be greater RPR at low magnitude events compared with conventionally developed urban watersheds without focused infiltration of stormwater.…”
Section: Discussionmentioning
confidence: 91%
“…The Spearman's correlation coefficients between PGR and climate-change indicators (temperature and the two extreme rainfall distribution indicators; see Table 3)highlight a general negative correlation between temperature (T) and PGR, with zero effect on the MED, SAH, and HORN regions, with a modest impact on SEQ (-0.20), and with a significant influence on NEQ (-0.48) and SAFR (-0.76) (Tashie et al, 2015). While the relationship between rainfall and temperature is difficult to characterize, the correlation between potential evapotranspiration (ET p ) and temperature is often positive (Kingston and Taylor, 2010).…”
Section: Inter-annual Variability Of Pgrmentioning
confidence: 99%
“…, Tashie et al. ). Further, landcover is commonly the only spatially explicit data type available over large geographic extents (Ivanov and Eigenraam , Kindu et al.…”
Section: Introductionmentioning
confidence: 99%